The Zombie Zone - Roy, Ron; Illustrated by Gurney, John Steven (New York Random House, 2005)
Reports of zombies and grave-robbers alarm the people of a Louisiana swampland village, but Ruth Rose, Josh, and Dink begin to suspect that the supernatural may not be the cause of the eerie occurrences.
Include Illustrations
Keywords: Detective and mystery stories -- Zombies